Black women in language teaching: decolonial provocations in Multiliteracies projects - Teixeira, Elisa Sodré; Costa, Ana Patrícia Sá Martins; Teixeira, Monaliza Sodré (The ESPecialist, 2025)
Anchored in the non-disciplinary perspective of Applied Linguistics and the conception of language as a dialogical and interactional construction, this article aims to analyze the construction of authorship in the process of didactic-digital literacies materialized in the praxiological writing of undergraduate students in didactic proposals for teaching language and literature, from a multiliterate and decolonial perspective. The didactic proposals were constructed from a didactic multiliteracies program at a public university in the southern region of Maranhão, in northeastern Brazil. They were gathered and systematized in an e-book entitled “Building didactic projects with digital technologies: learning beyond school”. Understanding that the aesthetic-formal position of authorship is materialized in an axiological relationship, we undertook documentary research with a qualitative approach, having as corpus chapters of the didactic material produced by the students, more specifically, those that addressed propositions about black women, who are invisible in the university in language teaching. We highlight the decolonial nature of the analysis by relating these issues to coloniality and by promoting their demystification through border positions, that is, approaches that articulate cultures, thoughts and identities of privileged spaces, such as European ones, with those that were/are historically invisible due to the colonial belief in the coexistence of differences. It is worth noting that the book analyzed is composed of multimodal resources, so in many moments, the teacher is directed to access complementary materials through digital elements.